ANALISIS KUALITAS PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KENDAL - Sila Hayuning Pawestri; Puji Astuti (Journal of Politic and Government Studies, 2026)
This study aims to analyze the quality of public services at the Department of Population and Civil Registration of Kendal Regency. This research employs a quantitative method with a descriptive approach by distributing questionnaires to 100 respondents who are users of population administration services. Data analysis was conducted using the Service Quality (SERVQUAL) method, which consists of five dimensions: tangibles, reliability, responsiveness, assurance, and empathy, to measure the gap between perceived service performance and public expectations. The results indicate that all SERVQUAL dimensions show negative gap values, suggesting that the quality of services provided has not fully met public expectations. The tangibles dimension shows the largest gap value, while the empathy dimension records the smallest gap. Therefore, improvements in service quality are necessary, particularly in terms of service facilities, timeliness, and the professionalism of service officers.